CONCEPTUAL APPROACH TO THE DEVELOPMENT OF INFORMATION SYSTEM OF OPERATIONAL MANAGEMENT OF EDUCATIONAL PROCESS IN HIGHER SCHOOL WITH THE USE OF CLOUD TECHNOLOGIES - L. I. Ostrinskaya; S. Yu. Pestova (Вестник СибАДИ, 2017)
Examines the conceptual approach to the development of the information system operating management of educational process in the University (IS OMEP UNIVTSITY), which is based on an OLAP-cube, service-oriented, client-server architecture and a platform that allows you to create online.  Personal accounts for the end users and participants of the educational process. For all groups of users are defined in a set of WEB Services, described their model, the proposed design solution based on the described business processes in BPMN notation.